تدريس مهارة الكلام في ضوء نظرية الذكاءات المتعددة بالتطبيق على تلاميذ مدرسة أناك صالح الابتدائية مالانج جاوى شرقية - Abdul Basid (Universitas Islam Negeri Palangka Raya, 2017)
AbstractThis reserach elaborates on the Arabic instruction, especially speaking skill based on Multiple Intelligences Theory. The research problems are: (1) what is the process of Arabic instruction based on Multiple Intelligences; and (2) what is the effectiveness of the use of Multiple Intelligence Theory in Arabic instruction, specially speaking skill. The design of this study is experimental study. Thus to get a focus, the researcher determines to use population and sample only for students who have word smart and auditory learning style by applying Multiple Intelligences Research. The result of this study is: (1) the process of speaking skill based on Multiple Intelligences Theory consist of personality, guideline (title, material, competence standard, indicator, period), procedure (scene setting, preface activity, main activity, closing activity), evaluation; (2) the result of speaking skill by using Multiple Intelligences theory in post test in experiment group is mean 79,16, paired different mean 23,33, standard deviation 7,35, standard error 3,00, t-test 5,534 and significant value 0,003 and the effectively level of the use of Multiple Intelligences theory in speaking skill is t-test 5,534, this level is higher than t-table 1% (2,11) and 5% (2,29).الكليمات الرئيسية: الذكاء، جوانب الذكاءات المتعددة، مهارة الكلام